Tackling pandemic-related health grand challenges: The role of organizational ambidexterity, social equality, and innovation performance - Christofi, Michael; Stylianou, Ioanna; Hadjielias, Elias; De Massis, Alfredo; Kastanakis, Minas N. (My University, 2024)
The outbreak of COVID-19 has brought the world to a standstill, with severe consequences on economic and health systems, requiring the identification and implementation of innovative solutions. This study's aims are threefold: first, to examine the impact of balanced and combined dimensions of ambidexterity on for-profit organizations' innovation performance related to pandemics; second, to uncover whether and to what extent such innovation performance contributes to tackling global health grand challenges (i.e., mortality rate, risk of infection, and life expectancy) associated with pandemics; and, third, to investigate the moderating role of social equalities in health in the relationships between innovation performance and health-related outcomes associated with pandemics. To uncover how for-profit firms tackle the health-related consequences of pandemics, we examine whether they have introduced product innovations to the health sector, defined as the market introduction of a new or significantly improved good, that have helped address the health challenges associated with the COVID-19 pandemic. Using a panel dataset (1974–2020) with 15,062 firm-year observations from the United States, we show that both the separate and the synchronous implementation of the balanced and combined dimensions of ambidexterity have a strong positive effect on firms' innovation performance and, particularly, innovation initiatives related to the pandemic. The results also reveal that innovation activities (i.e., granted patents and citations focused on COVID-19) negatively affect mortality rate and risk of infection, as well as the positive impact of innovation on increasing life expectancy, with social equalities in health moderating this relationship. Taken together, we make novel contributions to the literature on how to tackle the health-related consequences of pandemics through innovation and provide actionable managerial guidance on how firms can enhance innovation performance.
Keywords: COVID-19 pandemic; health care's grand challenge; innovation; organizational ambidexterity